Early Extended Midline Strip Craniectomy for Sagittal Synostosis. Issue 5 (July 2020) - O'Connell, John Edward; Ellenbogen, Jonathan; Parks, Chris
Abstract : Background: Isolated sagittal synostosis is the most common form of nonsyndromic craniosynostosis. The surgical management of this condition ranges from strip craniectomy to total cranial vault remodeling. In our unit, passive correction of sagittal synostosis utilizing open extended midline strip craniectomy with bilateral micro-barrel staving is performed before 22 weeks corrected age. The aim of this prospective study is to identify the effectiveness and morbidity associated with this technique. Patients and Methods: Nonsyndromic patients who underwent OMEC at a tertiaryreferral-center (Alder Hey Children's Hospital, Liverpool, UK) over a 3-year period (2014–2016) were included. In particular, we looked at pre- and postoperative cranial index (CI), as well as other secondary outcomes such as rates of transfusion and reoperation. Results: A total of 44 patients (12 female, 32 male) met the inclusion criteria. Median age at operation was 132 (range 99–171) days. Median operative time was 117 (range 89–171) minutes. Twenty-four patients underwent a blood transfusion. Median pre-op CI was 66 (range 61–74.7)%. The first post-op CI, taken a median of 56 (range 12–107) days postoperatively, was 78 (range 73–87)%. No patients required reoperation. There were no perioperative deaths. Conclusion: Early open extended midline strip craniectomy with bilateral micro-barrel staving for correction of isolated nonsyndromic sagittal synostosis is a safe and effective technique, associated with minimal morbidity, producing sustained satisfactory head shape morphology on short to medium-term follow-up.